INTEGRATED COMMUNITY PARTNERSHIP IN PROMOTING TOURISM VILLAGES IN PUJON KIDUL, INDONESIA - Adi Pradana, Mahatva Yoga; Asrul; Muhammad Mansur; Hanan Asrowy (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This qualitative research aims to learn about the political and institutional model of village heads in East Java in building networks in their villages. The theory developed in understanding political networks was carried out by McCaffrey and Salerno (2011), where the special interests of political entrepreneurs dominate a pattern of political entrepreneurship, incentives from the system built, and awareness about changing political institutions. In addition to the theory development carried out by Wawan Sobari (2019), political entrepreneurship requires leadership based on Javanese cultural values ​​and religious practices. This study found a middle ground regarding the existence of political partnerships by village youth to build village political institutions. In addition, this study also found a critical community culture that was formed within the village head network. Interconnection patterns of various stakeholders form a political network capable of creating a solid image for the local village leadership model. In this paper, the authors try to expand the study of entrepreneurial politics, where networks are needed to support leadership behaviour.